DIFFERENCES BETWEEN BIOCHEMICAL, HEMATOLOGICAL, AND COAGULATION PARAMETERS AMONG PATIENTS WITH MILD AND SEVERE COVID-19 - Hasanefendić, Berina; Dedić, Armina; Hajro, Sanela; Sehercehajic, Emir; Hajrović, Almedina; Alimanović-Alagić, Rubina; Smajlbegović, Velda; Ibričević-Balić, Lejla (Sanamed, 2023)
Introduction: COVID-19 is an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 and causes a series of respiratory symptoms. Considering the appearance and development of symptoms, the course of COVID-19 can go from mild to severe. Depending on the course of COVID-19, the laboratory parameters change a lot, trying to defend the organism against the foreign pathogen and all the changes it causes.Therefore, the aim of this study is to observe the differences between biochemical, hematological and coagulation parameters depending on the disease stage of COVID-19 patients. Material and methods: We conducted a cross-sectional study which included 160 COVID-19 patients from Sarajevo, Bosnia and Herzegovina. Biochemical, hematological and coagulation analyses were performed. Results: COVID-19 patients with a severe clinical course have higher average values of fibrinogen (6.53±4.47,p<0.001), D-dimer (6.89±7.81, p<0.001), APTT (32.05±5.96, p=0.002), eosinophil (0.66±0.09, p=0.002) and CRP (93.42±75.86, p= 0.023), and lower values of lymphocytes (1.04±0.98, p<0.001), monocytes (0.45±0.3, p<0.001), compared to COVID-19 patients with a mild clinical course. COVID-19 patients with a severe clinical course had higher average values of neutrophils (10.12±5.80, p=0.002) and lower values of reactive lymphocytes (0.02±0.03, p<0.001) compared to COVID-19 patients with a mild clinical course. Conclusion: Biochemical, hematological and coagulation parameters can be a sensitive and specific biomarker for distinction of mild and severe COVID-19.